Yatay Eksenli Çamaşır Makinalarında Titreşim Ve Gürültünün Azaltılması Amacıyla Aktif Ve Yarı Aktif Kontrol Uygulamalarının İncelenmesi - Yalçın, Barış Can (Fen Bilimleri Enstitüsü, 2014)
Tez çalışmasında, öncelikle yatay eksenli bir çamaşır makinasının çalışması sırasında oluşan titreşimler incelenmiş, yürüme kararlılığı davranışı oluşan titreşimlerin azaltılması ile iyileştirilmeye çalışılmıştır. Çamaşır makinasının yürüme davranışı gösterdiği sınır koşulları göz önünde bulundurulup, bu koşullar altında yürüme davranışı sergilememesi için uyarlamalı yarı aktif ve uyarlamalı aktif süspansiyon sistemi tasarımları önerilmiştir, bu tasarımların kullanılabilirliği (titreşim ve akustik çıktıları) simülasyon ve deney sonuçları ışığında tartışılmış, avantaj ve dezavantajları ortaya konmuştur. Birinci bölüm yürüme problemini doğuran yüklerin matematik ifadelerinin verilmesini, problemin çözümüne yönelik literatüre geçmiş çalışmaları ve tezin bu çalışmalardan farklı olarak problemin çözümüne dair geliştirdiği bakış açısının anlatımını içermektedir. İkinci bölüm, yürüme davranışının çamaşır makinasının sistem değişkenleri üzerinden matematik modelinin çıkarılmasını konu almaktadır, çamaşır makinasının sistem dinamikleri rijit ve rijit olmayan hal (süspansiyon sistemi ile birlikte) olarak iki farklı şekilde incelenmiştir. Aktif süspansiyon sisteminin kontrolü için önerilen model referans uyarlamalı kontrolcü tasarımının teorik alt yapısına ait bilgiler verilmiştir. Kontrolcü tasarımları MIT kuralı ve Lyapunov kuramı tabanlı olarak iki kısma ayrılmıştır, birinci ve ikinci dereceden sistemlerin modellenmesini içermektedir. Son olarak yarı aktif süspansiyon sisteminin kontrolünde kullanılan uyarlamalı kontrolcü yapısı açıklanmıştır. Üçüncü bölümde, ikinci bölümde verilen yürüme probleminin çamaşır makinası parametreleri üzerinden çıkarılan matematik modeli ile önerilen model referans uyarlamalı kontrolcü dinamikleri birleştirilmiş, elde edilen çıktıların yürüme probleminin iyileştirilmesine yönelik katkısı tartışılmıştır. Birinci dereceden sistem olarak modellenen süspansiyon elemanları üzerinde MIT ve Lyapunov tabanlı kontrolcüler uygulanmıştır. Dördüncü bölümde tez çalışmasında kullanılan yarı aktif süspansiyon sistemi tanıtılmıştır. Çalışma prensibi aktarılmış, tasarımda kullanımları halinde oluşabilecek avantaj ve dezavantajlar değerlendirilmiştir. Yarı aktif süspansiyon sistemi kontrolü kısmında kullanılan algılayıcı, motor sürücü devresi, veri toplama kartı ve uyarlamalı kontrol kuramına ait bilgiler verilmiş, algılayıcının yapısı, donanımı (çalışma aralığı ve hassasiyeti), programlanması, kullanımından doğan ekonomik avantajlar, veri toplama kartı ile haberleşmesi, veri toplama kartının donanımı ve bu ekipmanların çalıştığı uyarlamalı kontrol kuramı aktarılmıştır. Son olarak yarı aktif süspansiyon sistemi üzerinde kullanılan kontrol kuramı sonucu alınan titreşim ve akustik veriler değerlendirilmiştir. Beşinci bölümde, dördüncü bölümde alınan sonuçlar üçüncü bölümde aktif süspansiyon sistemi için simülasyon olarak hesaplanan yürüme kararlılığı çıktıları ile karşılaştırılmıştır.

In this thesis, firstly vibration parameters (angular position and angular acceleration parameters changing in time) occurred by a horizontal axis washing machine are investigated and walking stability behaviour is improved by reducing these vibration parameters. Origin of the success of suspension systems on dynamic stability is that  suspension systems can manipulate the centrifugal forces on the cabinet by storing and dissipating them, so the centrifugal forces produced by clothes are being transferred from drum onto the ground in a desired way. To change magnitude and direction of transferred forces means a contribution to stable dynamic behaviour of washing machine. MPU6050 is used as a motion sensor due to performance/cost ratio. The MPU6050 sensor combines a 3-axis gyroscope and a 3-axis accelerometer on the same silicon together with an onboard Digital Motion Processor capable of processing complex 9-axis MotionFusion algorithms. The parts integrated 9-axis MotionFusion algorithms access external magnetometers or other sensors through an auxiliary master I²C bus, allowing the devices to gather a full set of sensor data without intervention from the system processor. The devices are offered in the same 4x4x0.9 mm QFN footprint and pinout as the current MPU-3000™ family of integrated 3-axis gyroscopes, providing a simple upgrade path and making it easy to fit on space constrained boards. User programmable gyroscope scale is adjusted to ±2000 °/s and user programmable accelerometer scale is adjusted to ±16g. Even though data acquisition card provides 5V, sensor has a voltage regulator for its working voltage 3.3 V. Communication with data acquisition card is performed using I2C protocol at 400Hz from SCL and SDA channels. Software for communication is programmed in MATLAB using C programming language. The motion (gyroscope and accelerometer) sensor is located on top-front panel of the washing machine because of mathematical model of a horizontal axis washing machine suggests walking behaviour starts around this area under some assumptions, so that the calculation of vibrations occuring there is crucial. Arduino Mega 2560 is used as data acquisition card in this study, it includes ATmega microcontroller, communication between PC and data acquisition card is performed using serial communication protocol. Positive edge PWM signal is sent from digital pin of data acquisition card after receiving sensor data. Software for communication is programmed in MATLAB using C programming language. Considering boundary conditions at which washing machine starts showing walking instability behaviour, adaptive controller designs are proposed for semi-active and active suspension structures. For semi-active suspension system, study was completed with experiments, semi-active suspension elements are located under left and right sides of the tub. Before actuation signals are received by step motors, vibration data are evaluated and then step motors start to narrow or expand radius of bracelets located on suspension elements. This situation makes the semi-active suspension system to absorbe unwanted vibrations and contributes walking stability of washing machine. In evaluation process of vibration data, angular position and angular acceleration values in 3 axis (x, y, z) are weighted with different coefficients and defined in a function, maximum force produced by semi-active suspension elements are calculated according to the value of this function to ensure mathematical criteria of walking stability derived in this study. Experiments were performed for spinning cycle of washing machine which produces the most challenging vibration patterns for walking instability, angular velocity for this cycle is adjusted to 900 rev/min. Moreover, even though maximum cloth weight capacity of washing machine is 7 kg, it is loaded with 10 kg load to test control approach hardly. Moreover, sound power produced by the washing machine is measured to evaluate sound performance of washing machine while semi-active suspension system is controlled. An adaptive control method based on interpretation of vibrations is used. In this method, forces created by suspension elements are adjusted to have higher values when vibrations decrease and forces created by suspension elements are adjusted to have lower values when vibrations increase. The process of changing maximum forces of suspension elements can only be achieved at the same time due to the structure of motor drive module. A positive edge PWM (Pulse Width Modulation) signal is sent from data acquisition card to motor drive module passing through a circuit including a 3k resistor and a NPN transistor. The connection is between resistor and transistor is serial. For active suspension system, study was completed with simulations, model reference adaptive controller designs based on MIT rule and Lyapunov approach are used. Stability and system identification results from both methods are discussed and it has been proven that Lyapunov approach gives more stable and more accurate outputs. Effectiveness of controllers for semi-active and active suspension designs are discussed according to outputs of simulations and experimental results, advantages and disadvantages of the controllers are discussed. In first section, some studies in literature onto solve the walking instability problem are given. Differences of thesis in comparison with other studies are analyzed and contribution of thesis is explained. In second section, forces that cause walking instability behaviour are defined mathematically, a combined mathematical model of washing machine and walking instability behaviour containing system dynamics as parameters is derived, system dynamics of washing machine are assumed in two different ways; rigid and nonrigid cases (with suspension system) and relation between mathematical model and system dynamics is discussed. Fundamental information on theoretical structure of the model reference adaptive controller proposed to be used with active suspension system is given, as model reference adaptive controller based on MIT rule and based on Lyapunov approach, containing first and second order systems, and finally adaptive controller used on semi-active suspension system is given. In third section, mathematical model of walking instability behaviour with washing machine’s system dynamics is combined with model reference adaptive controller theory given in second section, adaptive model reference controllers based on MIT rule and based on Lyapunov approach are applied on active suspension system modelled as first order system, contribution of obtained outputs on walking stability is discussed. In fourth section, information about sensor, data acquisition card, motor drive module and structure of semi-active suspension are given. Hardware of sensor (sensitivity and bandwitdh), its programming code to communicate with data acquisition card are given and the implantation of adaptive controller structure using these equipments is explained. Vibration (angular position and angular acceleration) and acoustic outputs (sound power) of semi-active suspension system working with adaptive controller are given. In fifth section, outputs from experiments using semi-active suspension system are compared with simulation outputs obtained using active suspension design in third section.
Investigation Of Active And Semi-active Control Applications For Reducing Vibration And Noise On Horizontal Axis Washing Machines
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: Titreşim Ve Gürültü Kontrolü; Mekatronik; Çamaşır Makinası; Yarı Aktif Süspansiyon; Aktif Süspansiyon; Vibration And Noise Control; Mechatronics; Washing Machine; Semi Active Suspension; Active Suspension